2021
DOI: 10.1111/his.14335
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology at autopsy: why bother?

Abstract: Aims The frequency of histopathological sampling at autopsy varies, even though inadequate sampling may limit the value of autopsy reports. This study aims to investigate the contribution of histopathology at autopsy in a major teaching hospital. Methods and results A total of 532 coronial autopsy reports from Manchester Royal Infirmary were analysed retrospectively. Gross and microscopic diagnoses were compared and classified as concordant, discordant, histology needed (i.e. indeterminate or unremarkable gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Two earlier studies have found large effects of histology [6,7], whereas others have not [8][9][10]. The two studies with large effects [6,7] and one of the studies with a small effect [8] used unselected medico-legal populations. However, the paper with a small effect had a population where natural causes of death constituted only 23% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two earlier studies have found large effects of histology [6,7], whereas others have not [8][9][10]. The two studies with large effects [6,7] and one of the studies with a small effect [8] used unselected medico-legal populations. However, the paper with a small effect had a population where natural causes of death constituted only 23% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Histology is undoubtedly useful in natural deaths [4,5], but studies in a medico-legal setting have shown inconsistent results [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was reflected in the analysis, where the average number of lung sections in the study group was 5.4, and in the control group -6.3. Taking too few specimens or improperly preserving them (e.g., placing too large specimens in too small a volume of formalin) can result in failure to diagnose disease (including, but not limited to, pneumonia) in post-mortem examinations [28].…”
Section: Discussionmentioning
confidence: 99%
“…umieszczenie zbyt dużych wycinków w zbyt małej objętości formaliny) może skutkować nierozpoznaniem choroby (w tym m.in. zapalenia płuc) w badaniach post mortem [28].…”
Section: Discussionunclassified